2019
DOI: 10.35500/jghs.2019.1.e45
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of diarrhea of children under five in Malawi: based on Malawi Demographic and Health Survey 2015–2016

Abstract: Background: Diarrhea of children under 5 in Malawi, a high-burden country for diarrhea, accounted for 7% of under-5 mortality in 2017. Preceding studies have revealed the association between diarrhea of under-fives and characteristics of children and households including water, sanitation and hygiene (WASH). There has been limited household-level analysis regarding diarrhea in Malawi, thus the aim of our study is to identify risk factors of diarrheal disease among children under 5 in Malawi. Methods: Data set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 18 publications
7
13
3
Order By: Relevance
“…4 Some studies found that boys are more likely to get diarrhea than girls as they do more environmental activities. 4,13 This is contradictory to what was found in this study. This study supports studies by Yusuf 14 and Anyorikeya 6 that also found more female diarrhea patients than males.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…4 Some studies found that boys are more likely to get diarrhea than girls as they do more environmental activities. 4,13 This is contradictory to what was found in this study. This study supports studies by Yusuf 14 and Anyorikeya 6 that also found more female diarrhea patients than males.…”
Section: Discussioncontrasting
confidence: 93%
“…Diarrheal disease is most prevalent in children under the age of two, notably between the age of 12 and 23 months according to Moon et al. 13 Diarrhea case is particularly high between the age of 12 and 23 months because the maternal antibodies have started declining since birth. However, the immune system starts developing after the age of two from repeated environmental exposures.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study involving 347 households in rural Bangladesh showed that children U5 whose family members washed their hands with soap after defecation were significantly less likely to experience a diarrhea episode in the 48 h preceding the survey compared to children whose family members washed their hands with water only [ 26 ]. A cross-sectional study in Malawi, which used Demographic and Health Survey data, showed that the lack of soap in hand-washing facilities was associated with higher odds of having a diarrhea episode among children U5 [ 27 ]. In contrast, the main finding of the present study is not consistent with the findings of a study conducted in Saravan province of the Lao PDR.…”
Section: Discussionmentioning
confidence: 99%
“…The scoring factor of the asset was 0.301 for television, 0.357 for refrigerator, 0.334 for fan, 0.225 for water pump, 0.206 for air conditioner, 0.313 for washing machine, 0.191 for CD/DVD player/home theatre, 0.327 for iron, 0.347 for rice cooker/steam cooker, 0.246 for watch, 0.211 for bicycle, 0.196 for motorcycle/scooter, 0.005 for animal-drawn cart, 0.258 for car/truck/van, 0.044 for boat with a motor, and 0.060 for Tak Tak. Area In the LSIS II, area was divided into three categories: “urban,” “rural with road,” and “rural without road.” In the present study, “rural with road” and “rural without road” were combined into one category, titled “rural,” according to similar studies [ 27 ]. In the LSIS II, the definition of urban/rural followed the Lao Statistics Bureau’s village register in 2015: a village was classified as urban if it met at least three out of the following five conditions: (a) the village is situated in a district or provincial center, (b) more than 70% of the total households in the village use electricity, (c) more than 70% of the total households in the village use piped water, (d) the village is accessible by road throughout year, and (e) the village has a permanent market that is operating daily [ 41 ].…”
Section: Table A1mentioning
confidence: 99%
“…Inadequate quantities and quality of drinking water and lack of sanitation facilities cause the death of millions of the world’s poorest people through diarrheal diseases each year [ 9 , 10 ]. Furthermore, studies revealed that age of child [ 11 – 15 ], maternal education [ 11 , 12 , 16 ], lack of awareness of mothers/caregivers [ 17 , 18 ], lower socio-economic status [ 12 ], distance and source of drinking water [ 11 , 19 , 20 ], latrine and hand washing facilities [ 21 , 22 ], breast feeding [ 21 , 23 ], place of residence [ 14 , 22 , 24 ], disposal of children’s stool [ 24 26 ], family size [ 17 , 27 ], number of under-five children in the household [ 13 , 18 ], maternal age [ 19 , 20 ] and maternal employment status [ 13 , 17 , 19 , 28 ] as the determinant factors of diarrhea among under-five children.…”
Section: Introductionmentioning
confidence: 99%